Pesticides Recent Trends in Pesticide Residue Assay - Soundararajan, R.P (IntechOpen, 2012)
Growing population in the world demands increase in the food production and intense health care systems. Use of chemical pesticides is imperative for the management insects in agricultural and disease transmission, weeds and harmful microbes. Monitoring and estimating pesticide residue in crop plants, food, soil, water and other ecosystem has become significant in the recent concern on environment and ecosystem. The book comprises of new innovative trends to detect pesticide residue in crop plants, animal origin food and fishes. Different advanced extraction techniques of sample preparation for residue analysis are elaborately described. Apart from residue assays, metabolism and degradation of pesticide compounds fenamophos, chlorpyrifos, pirimiphos, heptachlor and organic pesticides are also documented. This book volume is of twelve chapters contributed by eminent scientists from eleven countries.